How Our Continuing Studies of the Pre-clinical Inbred Mouse Models of Mesothelioma Have Influenced the Development of New Therapies - Bruce W.S. Robinson; Bruce W.S. Robinson; Alec J. Redwood; Alec J. Redwood; Jenette Creaney; Jenette Creaney (Frontiers Media S.A., 2022)
Asbestos-induced preclinical mouse models of mesothelioma produce tumors that are very similar to those that develop in humans and thus represent an ideal platform to study this rare, universally fatal tumor type. Our team and a number of other research groups have established such models as a stepping stone to new treatments, including chemotherapy, immunotherapy and other approaches that have been/are being translated into clinical trials. In some cases this work has led to changes in mesothelioma treatment practice and over the last 30 years these models and studies have led to trials which have improved the response rate in mesothelioma from less than 10% to over 50%. Mouse models have had a vital role in that improvement and will continue to play a key role in the future success of mesothelioma immunotherapy. In this review we focus only on these original inbred mouse models, the large number of preclinical studies conducted using them and their contribution to current and future clinical therapy for mesothelioma.